The Optimum Mixed Cropping Ratio of Oat and Alfalfa Enhanced Plant Growth, Forage Yield, and Forage Quality in Saline Soil - Guanglong Zhu; Jiao Liu; Hao Wu; Yiming Zhu; Nimir Eltyb Ahmed Nimir; Guisheng Zhou (Plants)
The forage shortage is more aggravating than ever before, with husbandry development accelerating and meat and dairy product demand increasing. Salinized soils are important reserve land encouraged to be used for forage production in China. However, the salt-tolerant cultivation techniques for forage crops are still inadequate. Therefore, a field experiment was conducted to study the effects of the mixed cropping ratio of oat and alfalfa on plant growth and physiological traits, forage yield, and forage quality in saline soils. Oat (Avena sativa L.) variety of Canadian Monopoly and alfalfa variety of WL525HQ were used, and five mixed cropping ratios (T1 = 100% oat + 0% alfalfa, CK, T2 = 75% oat + 25% alfalfa, T3 = 50% oat + 50% alfalfa, T4 = 25% oat + 75% alfalfa, and T5 = 0% oat + 100% alfalfa) were evaluated. The results showed that plant height, chlorophyll, soluble sugar, starch, antioxidant enzymes, and crude fat were increased firstly and then decreased prominently with decreased oats and increased alfalfa sowing rate; the maximum values showed under T2 but the minimum value under T5 at evaluated growth periods. On the contrary, malondialdehyde and acid detergent fiber were significantly decreased and then increased; the lowest contents were recorded under T2 and highest under T5. Furthermore, the relative growth rate, forage yield, neutral detergent fiber, and crude ash were decreased prominently with decreased oats and increased alfalfa sowing rate, and the highest and lowest values showed under T1 and T5, respectively. Oppositely, the contents of sucrose, proline, N, P, K, relative feeding value, and crude protein were all increased, with the highest contents generated under T2 and the lowest under T1. On the whole, the mixed cropping treatment of T2 showed the best performance in improving both biomass yield and forage quality by enhanced antioxidant enzyme activity, osmotic regulatory substances, and nutrient uptake and utilization. Therefore, this study indicates that 75% oat mixed cropping with 25% alfalfa can be recommended as a salt-tolerant cultivation technique for forage high-yield and high-quality production in moderately saline soil.